"تأثير أنواع ومعدلات مختلفة من السماد العضوي على الخصائص الإنتاجية والمورفولوجية للقمح القاسي في الساحل السوري" (Latakia University Journal -Biological Sciences Series, 2017)
نُفِّذت التّجربة في مركز بوقا الزراعي، التابع لجامعة تشرين, في محافظة اللاذقية, خلال الموسم الزراعي (2014), بهدف دراسة تأثير أنواع (بقر, غنم, دواجن) ومعدلات (0, 15, 30 طن/ه) مختلفة من السماد العضوي على القمح القاسي (دوما1), وتمت الزراعة بتاريخ (23/11/2014)، وفق نظام القطاعات العشوائية الكاملة (27 مكرر)، وتمت إضافة السماد ضمن خطوط الزراعة (6/10/2014)، وقد أظهرت النتائج استجابة لمتوسط جميع الصفات المدروسة (الكثافة النباتية (نبات/م2), طول النبات (سم), طول السفا (سم), وزن الحبوب/السنبلة (غ), وزن الـ1000 حبة (غ)) بشكل إيجابي للتسميد العضوي، في حين لم تسجل فروق معنوية في المتوسطات للصفات المدروسة (الكثافة النباتية (نبات/م2), طول النبات (سم), طول السفا (سم), وزن الحبوب/السنبلة (غ), وزن الـ1000 حبة (غ)) تحت نوع السماد العضوي، أما في حالة التداخل بين نوع ومعدل السماد العضوي فقد سجلت فروق معنوية وعالية بين المعاملات, إذ كانت معاملة (30 طن/ه دواجن) الأكثر تأثيراً على جميع الصفات المدروسة, حيث أعطت النتائج التالية: الكثافة النباتية (331.70 نبات/م2), طول النبات (95.85 سم), طول السفا (16.24 سم), وزن الحبوب/السنبلة (1.66 غ), وزن الـ1000 حبة (49.57 غ).The experiment carried out in the agricultural Center (Boqa) of Tishreen University, in the province of Lattakia, during the agricultural season (2014), in order to study the effect of different types (cattle, sheep, poultry) and rates (0, 15.30 ton/ha) of the compost on durum wheat (Doma1). It farmed on (11.23.2014), according to complete system of randomized sectors (27 bis).The compost was added within the lines of Agriculture (10/06/2014). The results showed a response to the average of all the studied traits (plant density (plant/m2), plant height (cm), the length of awn (cm), grains/spike weight (g), the weight of 1000 grains (g)) positively organic fertilizing. While no significant differences were recorded in the averages of the traits studied (plant density (plant/m2), plant height (cm), the length of awn (cm), grains/spike weight (g), 1000 grains weight (g)) under the manure type. In the case of overlap between the type and the rate of organic manure, it has recorded a significant and high differences between the treatments. The treatment (30 ton/ha-1 poultry) was the most influential of all the studied traits. It gave the following results: plant density (331.70 plants/m2), plant height (95.85cm), the length of awn (16.24 cm), grains/spike weight (1.66 g), 1000 grains weight (49.57 g).